1989
DOI: 10.2224/sbp.1989.17.2.135
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Romantic Jealousy Among Black Undergraduates

Abstract: This study examined the relationship between jealousy and self-esteem, insecurity, external locus of control and sex. The sample consisted of 128 undergraduates who completed four self report inventories. A step-wise multiple regression analysis indicated that self-esteem and insecurity accounted for 28% of the total variance in jealousy. Contrary to prediction, however, external locus of control did not account for a significant amount of the variance in jealousy. Results are discussed in terms of the contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…However, both sides in the relationships try to save their relationships and suffer from depression as a consequence of jealousy. These findings match with those of (Gary and Hansen, 1985;McIntosh, 1989;White 1981a andMullen, 1989).…”
Section: The State Of Jealousy and Jealousy Reactionssupporting
confidence: 90%
“…However, both sides in the relationships try to save their relationships and suffer from depression as a consequence of jealousy. These findings match with those of (Gary and Hansen, 1985;McIntosh, 1989;White 1981a andMullen, 1989).…”
Section: The State Of Jealousy and Jealousy Reactionssupporting
confidence: 90%
“…initially, some studies found no correlation between self-esteem and romantic jealousy (Buunk, 1981;White, 1981). later on, a negative correlation was found (Buunk, 1982;Khanchandani & Durham, 2009;Mcintosh, 1989;salovey & rodin, 1991). Most research on the subject has been conducted with explicit (controlled, conscious) measures of self-esteem, without taking into account the recent development of measures of implicit aspects (e.g.…”
Section: Personal Variablesmentioning
confidence: 99%
“…Empirical studies on jealousy and personality have particularly linked jealousy to personality characteristics such as insecurity and self-esteem, and have found that, as individuals are more insecure or have lower self-esteem, they report higher levels of jealousy (e.g., Jaremko & Lindsey, 1979;McIntosh, 1989;Mullen, 1994;Nadler & Dotan, 1992). Related, there is consistent evidence for a positive association between jealousy and neuroticism (e.g., Buunk, 1981Buunk, , 1997Dijkstra & Barelds, 2008;Mathes et al, 1982;Melamed, 1991;Tarrier et al, 1989;Xiaojun, 2002).…”
Section: Jealousy and Personalitymentioning
confidence: 99%